Study of the Physiological Responses of Two Strains of Laying Hens under Thermal Challenge - Dalila Hammouche; Abdelhak Karim Mouss; Rahla Meziane; Hacene Ikhlef (Biology and Life Sciences Forum)
The breeding of laying hens has been profoundly transformed by various factors from genetic selection to the development of infrastructure, including nutritional and health management, making this activity a pillar of the food chain. However, temperature fluctuations, which are increasingly frequent due to climatic upheavals, pose significant challenges to production systems. Thermal challenges could have harmful consequences for physiological responses, thus impacting the ability to produce eggs optimally. In this general context, the work presented aims to study specific aspects of the physiological responses in two strains of laying hens, Novogen Brown and Isa Brown. The birds were maintained under thermal challenge, and measurements of the blood lipid profile and laying performance were carried out from the 26th to the 36th week of age at the rate of a sample every 15 days. The results revealed that the Novogen Brown strain presents significantly lower cholesterol levels than the Isa Brown strain when considering all samples (2.02 ± 0.09 vs. 2.45 ± 0.04 g/L; p = 0.0098). This general trend in the results was also observed for triglyceride levels, with respective means of 1.99 ± 0.02 vs. 2.12 ± 0.08 g/L; p = 0.034. The production indicators were in favor of the Novogen Brown strain, where significant increases in the laying rate were recorded (82.33 ± 3.32 vs. 79.82 ± 4.21%; p = 0.0041), of egg weight (59.98 ± 1.33 vs. 57.23 ± 2.32; p = 0.00097), as well as a reduction in the breakage rate (4.99 ± 0.23 vs. 6.02 ± 0.58%; p = 0.021) and mortality rate (6.41 ± 1.11 vs. 8.23 ± 2.22; p = 0.016). All the results also highlighted physiological responses that materialized due toa disturbance in the lipid balance, which impacted the entire production process.